FT-IR spectroscopy for the detection of liver damage. Issue 1 (2004) - Crupi Crupi, V. V.; Majolino Majolino, D. D.; Migliardo Migliardo, P. P.; Mondello Mondello, M. R. M. R.; Pergolizzi Pergolizzi, S. S.; Venuti Venuti, V. V.
Abstract : A spectroscopic analysis of hepatotoxic effects on rat liver, caused by a single administration of carbon tetrachloride (CCl4 ), has been performed by Fourier Transform Infrared (FT-IR) absorption technique in a wide range of frequency 3000–400 cm –1 . The spectral investigation has permitted us to mark the dynamical changes of rat liver samples vs. the time course of the injuries. In particular as lower frequency is concerned, the comparison among the control sample and the injured ones has revealed a clear change in the typical lipids stretching region 1800–1000 cm –1 . Furthermore, in the CH stretching region 3000–2400 cm –1, we showed a clear change in the band shape. The observed variations, respect to the normal liver case, have been interpreted on the basis of previous structural and biochemical analysis and in the framework of a recent FT-IR analysis of the O–H stretching region 3800–3000 cm –1 .